2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20180143
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on alopecia areata

Abstract: <p class="abstract"><strong>Background:</strong> Alopecia areata (AA) is a common auto-immune condition, causing hair loss. This disease has limited treatment modalities. Through this study, comparison between established modalities of treatment such as oral mini pulse therapy, intralesional corticosteroids and platelet-rich plasma (PRP) as a newer modality has been done. The objective of the study was to evaluate the efficacy and safety of various treatment modalities in alopecia areata.<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…23 The mean grading score of 3.57 is significantly higher in group I patches as compared to group II (2.63) at fourth follow-up. 24 Another Indian study by Agrawal et al also reported the response of intralesional triamcinolone acetonide (33.3%) for the treatment of scalp AA to be better than with intralesional PRP therapy (3.33%). 25 In a study by Shumez et al, PRP had an earlier response at the end of 6 weeks as compared to triamcinolone; however, this difference was statistically insignificant which is opposite to index study result.…”
Section: Discussionmentioning
confidence: 98%
“…23 The mean grading score of 3.57 is significantly higher in group I patches as compared to group II (2.63) at fourth follow-up. 24 Another Indian study by Agrawal et al also reported the response of intralesional triamcinolone acetonide (33.3%) for the treatment of scalp AA to be better than with intralesional PRP therapy (3.33%). 25 In a study by Shumez et al, PRP had an earlier response at the end of 6 weeks as compared to triamcinolone; however, this difference was statistically insignificant which is opposite to index study result.…”
Section: Discussionmentioning
confidence: 98%
“…These GFs are believed to stimulate stem cells sited in HF at the bulge areas leading to growth of fresh follicles and enhancing angiogenesis [13], [15]. Despite of its promising results in AA, a paucity of randomized controlled clinical trials had been published to assess the efficiency of PRP in management of AA [9], [13], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], 29], [30], [31], [32], [33], [34], [35]. Photobiomodulation (PBM), or low-level laser (or) light therapy (LLLT) is using red light (600-700 nm) or near infrared (700 nm-1000+nm) which is obtained from 5 to 500 mW light-emitting diode (LED) source [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…It symptomatically can be correlated to Alopecia Areata [2]. Alopecia Areata is hypothesized to be an organ specific autoimmune disease mediated by T lymphocytes directed to the hair follicles and of unknown aetiology [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ipomoea carnia jacq, belongs to convolvulaceae family found everywhere in India which is native of tropical America [9] and the main character of the plant is that it can regenerate very fast from its part in dry as well as the moist surfaces. Due to this unique character this plant is locally termed as thethar or besharam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation